Ammonia Electrosynthesis with a Stable Metal‐Free 2D Silicon Phosphide Catalyst. Issue 10 (23rd December 2022) - Lv, Chade; Jia, Ning; Qian, Yumin; Wang, Shanpeng; Wang, Xuechun; Yu, Wei; Liu, Chuntai; Pan, Hongge; Zhu, Qiang; Xu, Jianwei; Tao, Xutang; Loh, Kian Ping; et al.
Abstract: Metal‐free 2D phosphorus‐based materials are emerging catalysts for ammonia (NH3 ) production through a sustainable electrochemical nitrogen reduction reaction route under ambient conditions. However, their efficiency and stability remain challenging due to the surface oxidization. Herein, a stable phosphorus‐based electrocatalyst, silicon phosphide (SiP), is explored. Density functional theory calculations certify that the N2 activation can be realized on the zigzag Si sites with a dimeric end‐on coordinated mode. Such sites also allow the subsequent protonation process via the alternating associative mechanism. As the proof‐of‐concept demonstration, both the crystalline and amorphous SiP nanosheets (denoted as C‐SiP NSs and A‐SiP NSs, respectively) are obtained through ultrasonic exfoliation processes, but only the crystalline one enables effective and stable electrocatalytic nitrogen reduction reaction, in terms of an NH3 yield rate of 16.12 µg h −1 mgcat. −1 and a Faradaic efficiency of 22.48% at −0.3 V versus reversible hydrogen electrode. The resistance to oxidization plays the decisive role in guaranteeing the NH3 electrosynthesis activity for C‐SiP NSs. This surface stability endows C‐SiP NSs with the capability to serve as appealing electrocatalysts for nitrogen reduction reactions and other promising applications. Abstract : In this work, a new metal‐free 2D silicon phosphide electrocatalyst for ammonia synthesis under ambient conditions is reported. Such phosphorus‐based materials possess good chemical stability by suppressing surface oxidation. The surface protection guarantees the N2 activation and the protonation processes on the zigzag P sites. In neutral electrolyte, the crystalline SiP nanosheets enable high‐efficiency nitrogen reduction reactions for ammonia electrosynthesis.